One‐Step Access to Sequence‐Controlled Block Copolymers by Self‐Switchable Organocatalytic Multicomponent Polymerization - Ji, He‐Yuan; Wang, Bin; Pan, Li; Li, Yue‐Sheng (Angewandte Chemie International Edition, 2018)
A one‐step procedure for the self‐switchable block copolymerization of monomer mixtures of epoxides, cyclic anhydrides, and lactide (LA) was developed by using simple organocatalysts without an external stimulus. This multicomponent polymerization bridges two catalytic cycles involving ring‐opening alternating copolymerization of epoxides with anhydrides and ring‐opening polymerization (ROP) of LA, in which the presence/absence of anhydrides in mixed feedstocks switched the ROP of LA off/on. The self‐switchable terpolymerization showed distinct noncoordinating and living nature, as well as perfect chemoselectivity. Different combinations of epoxides, anhydrides, and initiators enabled the generation of a variety of new block polyester polyols. Admirable self‐control: A self‐switchable route to multiblock copolymers from three‐component feedstocks (see picture) was developed with commercially accessible organocatalysts. The one‐step procedure showed perfect chemoselectivity, living nature, and applicability to a wide range of monomers.